18F-Fluoroethylcholine (18F-Cho) PET/MRI Functional Parameters in Pediatric Astrocytic Brain Tumors. (January 2015) - Fraioli, Francesco; Shankar, Ananth; Hargrave, Darren; Hyare, Harpreet; Gaze, Mark N.; Groves, Ashley M.; Alongi, Pierpaolo; Stoneham, Sara; Michopoulou, Sofia; Syed, Rizwan; Bomanji, Jamshed B.
Abstract : Purpose: To examine the feasibility of simultaneous acquisition of 18 F-fluoroethylcholine ( 18 F-choline) PET and functional MRI (standardized uptake value [SUV]max/mean and apparent diffusion coefficient [ADC]mean ), using a hybrid PET/MRI scanner, for diagnosis and response assessment in a cohort of children with astrocytic brain tumors. Methods: 18 F-choline PET/MRI scans were performed in 12 patients with proven astrocytic tumors. Eight patients simultaneously underwent 18 F-choline PET/MR follow-up scans after treatment. Uptake in the lesion above the normal brain activity was considered indicative of a positive scan. Maximum and mean SUVs (SUVmax and SUVmean ) and mean ADC (ADCmean ) of the whole tumor region of interest were assessed. Lesion size and contrast enhancement were recorded. For all tumors, the association between ADCmean and SUVmean /SUVmax values were assessed using the Spearman correlation coefficient. Results: At baseline, the areas of 18 F-choline uptake matched areas of contrast enhancement and restricted diffusion. There was a negative correlation trend between SUVmax and ADCmean and a positive correlation trend between SUVmax and tumor size. There was concordance between reduction in tumor size and reductions in SUVmax and SUVmean in 4 children, in three of whom ADCmean values were increased. In 2 patients, tumor size remained stable whereas SUVmax and SUVmean values were increased with reduction in the ADCmean values. Additionally, in 2 children, cross-sectional MRI showed an increase both in tumor size and SUVmax but a reduction in ADC values. Conclusions: Simultaneous 18 F-choline PET/MRI is a promising and reliable imaging tool for children with astrocytic tumors, as it permits monitoring of morphological and metabolic response and changes during therapy.